Korelasi Kadar Vitamin C, Cholecalciferol dan Kadar Malondialdehid Antara Kejadian Abortus Dengan Kehamilan Normal : Studi Observasional - Manila, Hartati Deri; Yona Amir , Aprima; Meysetri , Fafelia Rozyka (Journal of Pharmaceutical and Sciences, 2025)
Introduction: Abortion is a pregnancy complication that contributes significantly to maternal morbidity and mortality. Approximately 73 million abortions occur annually worldwide, with the estimated abortion rate in Padang city in 2024 reaching 58.7%. Abortion remains a challenge in obstetrics. The relationship between vitamin C deficiency, cholecalciferol, and elevated MDA levels and abortion remains debated, given the complex pathophysiological mechanisms. Objective: to determine the correlation between vitamin C, cholecalciferol, and malondialdehyde levels between abortion and normal pregnancy. Method: This study is a comparative study of two unpaired groups with a cross-sectional approach to analyze the average levels of Vitamin C, cholecalciferol, and MDA. The population in this study was pregnant women diagnosed with abortion and all women with normal pregnancies with a gestational age of ≤ 20 weeks who were treated in the delivery room of RSUD dr. M. Zein, RS. dr. Reksodiwiryo Padang, RSUP M. Djamil Padang, RS. Rasidin Padang with a sample size of 30. Data analysis was carried out using an Independent Samples T-test. Results: The results of this study showed that Vitamin C levels were lower in the abortion group than in the control group, a significant difference (p = 0.001). Cholecalciferol deficiency was more pronounced in the abortion group, a significant difference compared to normal pregnancies (p = 0.002). MDA levels were very high in the abortion group, a significant difference (p = 0.001). Conclusion: There is a significant correlation of Vitamin C and cholecalciferol levels between the occurrence of abortion and normal pregnancy, and there is a significant correlation of malondialdehyde levels between normal pregnancy and the occurrence of abortion.